Pseudochelin A, a siderophore of Pseudoalteromonas piscicida S2040. Issue 18 (4th May 2017) - Sonnenschein, Eva C.; Stierhof, Marc; Goralczyk, Stephan; Vabre, Floriane M.; Pellissier, Leonie; Hanssen, Kine Østnes; de la Cruz, Mercedes; Díaz, Caridad; de Witte, Peter; Copmans, Daniëlle; Andersen, Jeanette Hammer; Hansen, Espen; et al.
Abstract: A new siderophore containing a 4, 5-dihydroimidazole moiety was isolated from Pseudoalteromonas piscicida S2040 together with myxochelins A and B, alteramide A and its cycloaddition product, and bromo- and dibromoalterochromides. The structure of pseudochelin A was established by spectroscopic techniques including 2D NMR and MS/MS fragmentation data. In bioassays selected fractions of the crude extract of S2040 inhibited the opportunistic pathogen Pseudomonas aeruginosa . Pseudochelin A displayed siderophore activity in the chrome azurol S assay at concentrations higher than 50 μM, and showed weak activity against the fungus Aspergillus fumigatus, but did not display antibacterial, anti-inflammatory or anticonvulsant activity. Graphical abstract: